Pengaruh Sistem Pengukuran Kinerja dan Disiplin Kerja terhadap Kinerja Pegawai Bea dan Cukai dalam Pengawasan Rokok Ilegal - Abbas Mansyur; Yulianto Yulianto (Majalah Ilmiah Bijak, 2020)
According to law enforcement in excise sector, customs and excise officers are supervise on illegal cigarettes. The main purpose is to diminish illegal cigarettes and optimizing revenue in excise from cigarettes sector. Enforcement was intensively on illegal cigarettes throughout 2014-2016, shown by 902 cases increase to 2.409 cases. In contrary, illegal cigarettes increased throughout 2014-2016 from 11,73% to 12,14%. Those illegal cigarettes also causing affect to revenue in excise from cigarettes sector, primarily in 2016 while target realization 100,02% only, because revenue was collecting Rp137.969.225.430.00 from target set at Rp137.935.634.471.520. Discrepancy between sum of cases on illegal cigarettes, illegal cigarettes and revenue in excise from cigarettes sector becomes an interesting research topic. This research employs survey method which population are customs and excise officers work on enforcement unit in Indonesia. Sampling method is probability on cluster sampling to collect quantitative data and analyzed those data summarize using descriptive and verification approach to find out the effect of performance measurement system and work discipline to performance of customs and excise officers in supervision illegal cigarettes. This research concludes performance measurement system and work discipline give a positive and significant effect to customs and excise officers’ performance in supervision and reducing illegal cigarettes and optimizing revenue in excise from cigarettes sector